Metabolite Profiles of Heart Failure, Central Hemodynamic Derangement, and Response to Heart Transplantation - Lejonberg, Carl; Czuba, Tomasz; Egerstedt, Anna; Ghosh, Nilanjana; Celik, Selvi; Lundgren, Jakob; Radegran, Goran; Gidlof, Olof; Smith, J. Gustav (Journal of the American Heart Association, 2025)
BACKGROUND: Heart failure (HF) is characterized by hemodynamic derangements that are likely to mediate systemic metabolic perturbations but limited data are available. Plasma metabolite profiling provides opportunities for comprehensive investigation of such perturbations. Here, we aimed to characterize plasma profiles that associate with HF and their relationship with central hemodynamics, symptom burden, and response to restoration of cardiac function by heart transplantation. METHODS: Untargeted metabolite profiling was conducted with mass spectrometry in 2 independent case–control samples. RESULTS: In total, 89 of 797 studied metabolites were significantly associated with HF in both cohorts with concordant directionality. Amino acid, carbohydrate, and nucleotide metabolites were enriched for association with HF and were consistently increased in HF cases. A subset of patients with advanced HF subsequently underwent heart transplantation, after which 17 of the 89 metabolites returned significantly toward healthy control levels. These 17 metabolites represent increased catecholamine and heme metabolism, conjugated bile acids, kynurenine pathway mediators, spermidine metabolism, and allantoin, as well as tricarboxylic acid cycle and glycolysis intermediates. Most of these metabolites associated with symptom burden and at least 1 of 12 central hemodynamic parameters, primarily relating to either increased systemic or pulmonary venous congestion, lower cardiac output, or lower left ventricular stroke work. CONCLUSIONS: We comprehensively identified metabolite profiles associated with HF and central hemodynamics that reverse by cardiac transplantation. Increased levels of most metabolites also associated with higher symptom burden. Our findings provide perspectives on the metabolic consequences of HF with potential implications for noninvasive monitoring and tailored therapy.
Publisher Copyright: © 2025 The Author(s). Published on behalf of the American Heart Association, Inc., by Wiley. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.
Keywords: heart failure; hemodynamics; metabolomics; transplantation